AN INVESTIGATION OF SOUND ABSORPTION PROPERTIES OF THE. PLAIN AND SPACER WEFT KNITTED FABRICS - (:unkn) unknown (UNIV ZAGREB, FAC TEXTILE TECH, 2010)
Sound absorption constitutes one of the major requirements for human comfort today. Sound insulation requirements in automobiles, manufacturing environments, and equipment, generating higher sound pressure drive the need to develop more efficient and economical ways of producing sound absorption materials. This frequencies ranges are under 4000Hz and between 100-1000Hz. Nonwovens have also been used, but they have a lesser aesthetic appearance and drapability compared with woven and knitted structures. On the other hand, similar sound absorption level might be obtained with plain weft knitted fabrics which are less thick than nonwoven structures. In the study; we tested the sound absorption properties of various plain and spacer weft knitted fabrics produced by 7G flat knitting machines. Sound insulation and sound absorption properties of the plain and spacer weft knitted fabrics produced by different patterns and yarns were investigated. Sound transmission loss was measured by Bruel and Kjaer PULSE sound test device according to ISO 10534-2 and ASTM E1050-98 standards.
Keywords: flat knitting fabric; sound absorption; spacer knitted fabrics; FIBER; COMPOSITE